A (DES) aglutinação sintático-semântico-discursiva: um enfoque enunciativo do verbo intransitivo em reportagens impressas - Nóbrega, Fabíola (2015)
The syntactic-semantic-discursive agglutination is a process concerning to the junction of the complement in the verb designed by Traditional Grammar (GT) as intransitive, having no material occupation as the object. However, in some situations, these verbs can be used like complement materialized in the syntax plan, with the syntactic-semantic-discursive detachment. This phenomenon is caused by enunciative reasons. Therefore, we had as main objective to analyze the syntactic-semantic-discursive agglutination and detachment of the verbs defined by the Traditional Grammar in an enunciation perspective, using, for this, printed reports. In order to answer this need, we developed the following specific objectives: to characterize the syntactic-semantic-discursive agglutination/ detachment as an enunciative phenomenon; analyze the meaning of a linguistic element (the verb) through two biases: theme (contextual meaning) and linguistic significance (in dictionaries sense) by combining with the active comprehension; understand how the syntactic-semantic-discursive agglutination and detachment are used in targeted verbs in a printed report, observing the thematic content, compositional elements and the style; discuss the factors that provide the syntactic-semantic-discursive agglutination the syntactic-semantic-discursive detachment in selected verbs for analysis. For this purpose, we used the theoretical construct defended by Bakhtin / Voloshinov (1981, 1926), Bakhtin (2003), as well as researchers of the linguistic thought from the Bakhtin Circle. Our corpus comprised twenty-two printed reports of Veja magazine, published in the period from 1968 to 2013 and selected in <http://veja.abril.com.br/acervodigital>. At first, we discuss the thematic content, compositional elements and the style of chosen reports. Subsequently, we analyze the syntactic-semantic-discursive agglutination in the verbs die, live, sunrise, fall, mature, aging, fight, react, dream, cry, smile, sleep, grow and laugh. And subsequently, we described some of the syntactic-semantic-discursive detachment in some of these verbs. Thus, we can say that, in this work, a syntactic phenomenon (the intransitive verbs) was observed by the Theory of Enunciation, according to Bakhtin / Voloshinov (1981).